Creating a Three-Dimensional Model of Objects of Cultural Heritage in a Modern Way - Yarashovich, Sattorov Shahzod; Muzaffarovich, Abdullaev Ashraf; Jaxongir, Kamolov; Abdulla, Akhrorov; Temur, Ismatov (European Journal of Life Safety and Stability (2660-9630), 2021)
This article provides information on the use of advanced technologies in the performance of Geodetic and geo informatic work, as well as the advantages of this software.